1995
DOI: 10.2190/yaa7-3c7g-tvxt-vatb
|View full text |Cite
|
Sign up to set email alerts
|

Age and Responses to the Love Attitudes Scale: Consistency in Structure, Differences in Scores

Abstract: Two separate issues concerning the relation between age and love are addressed in this article. The first issue is concerned with the age generalizability of the factor structure produced by responses to the Love Attitudes Scale. The data presented indicate that the factor structure of responses to the Love Attitudes Scale is highly similar in college-aged and middle-aged participants. The second issue concerns the relation between age and actual scores on the sub-scales of the Love Attitude Scales. The data i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Inconsistent findings from previous research were found regarding the relationship between age and Agape (e.g., Bierhoff & Rohmann, 2000;Butler et al, 1995;Montgomery & Sorell, 1997). It was not clear from the results of previous research whether age was positively, negatively or U-shaped related to Agape.…”
Section: Li-wen Lin and Catherine A Huddleston-casas 39mentioning
confidence: 58%
See 1 more Smart Citation
“…Inconsistent findings from previous research were found regarding the relationship between age and Agape (e.g., Bierhoff & Rohmann, 2000;Butler et al, 1995;Montgomery & Sorell, 1997). It was not clear from the results of previous research whether age was positively, negatively or U-shaped related to Agape.…”
Section: Li-wen Lin and Catherine A Huddleston-casas 39mentioning
confidence: 58%
“…However, results from past research on age differences and Agape were inconsistent. Some research suggested that older individuals were less agamic (Butler, Walker, Skowronski, & Shannon, 1995;Schultz, Joo, & Toews, 2001), while Bierhoff and Rohmann (2000) found a U-shaped relationship between age and Agape. They found that individuals between the ages of 35 and 45 years old showed the lowest level of Agape, compared to individuals between the ages of 19 and 35 years old, and 45 and 54 years old.…”
Section: Introductionmentioning
confidence: 99%
“…A study carried out by Butler et al (1995) also used the Love Attitude Scale (LAS) to analyze the relationship between love styles and other variables such as gender, age, various social factors and culture. Findings indicated that women were prone to adopt Storge (friendship love) and Pragma (pragmatic love) love styles whereas, males were prone to adopt Ludus (playful love) and Agape (altruistic love) love styles.…”
Section: Introductionmentioning
confidence: 99%
“…In effect, a decrease in agape love, as one matures may simply be the result of being less idealistic and having a more realistic view of relationship. Older people, especially females are less selfless and less possessive and dependent than people at younger ages (Butler, Walker, Skowronski, & Shannon, 1995). Therefore, based on the literature, it is hypothesized that the older a person gets, the more anger and hate will be present toward a former spouse.…”
Section: Predisposition Toward Anger a Predisposition Toward Anger (mentioning
confidence: 99%